Flame versus air atmospheric gliding arc plasma treatment of polypropylene‐based automotive bumpers: Physicochemical characterization and investigation of coating properties. Issue 5 (12th April 2021) - Shabanpour, Majid; Mohammadhosseini, Babak; Khani, Mohammad Reza; Khanjani, Jaber; Shokri, Babak; Ghassami, Amirreza
Abstract: In this research, the polypropylene (PP) sheets used for automotive bumper surface were treated using two methods: air atmospheric gliding arc plasma and flame modifications. Atomic force microscopy was applied to study the morphology of surfaces before and after treatment processes. While calculating the surface free energy (SFE), contact angle of the surfaces was measured, and the chemical composition of the PP surface was analyzed using X‐ray photoelectron spectroscopy. Surface modifications by gliding arc plasma increased the ratio of the oxygen and nitrogen atoms on the surface by 100%, indicating that polar chemical functionalities form on the surface. The surface morphology was highly affected by gliding arc plasma treatments, which triggered an impact on roughness and etching. It was also found that the SFE was drastically increased by certain modifications. Noticeable improvement was also observed in wettability by the gliding arc plasma technique. In the next stage, polyurethane paints were coated on the treated and untreated PP surfaces. Then, we examined the flame and gliding arc plasma treatments' effect on coating properties of PP bumper, adhesion analysis, water immersion resistance, and sulfuric acid resistance. Finally, high‐pressure carwash test and gloss analysis were conducted on the treated and untreated coated sheets, respectively. Abstract : Gliding arc plasma treatment of automotive bumpers is investigated in this study. At first, polypropylene surface was studied after plasma induction and surface properties such as roughness, surface free energy and functional groups moieties were evaluated. Then, coating properties of these surfaces were surveyed via car wash test, adhesion and gloss.